Fitness to fly for children and adolescents after Fontan palliation - Müller, N.; Herberg, U.; Breuer, J.; Kratz, T.; Härtel, J. A. (Frontiers in Cardiovascular Medicine, 2023)
Introduction At cruising altitude, the cabin pressure of passenger aircraft needs to be adjusted and, therefore, the oxygen content is equivalent to ambient air at 2,500 masl, causing mild desaturation and a rising pulmonary vascular resistance (PVR) in healthy subjects. For Fontan patients with passive pulmonary perfusion, a rising PVR can cause serious medical problems. The purpose of this fitness to fly investigation (FTF) is to assess the risk of air travel for children and adolescents after Fontan palliation. Methods We investigated 21 Fontan patients [3–14y] in a normobaric hypoxic chamber at a simulated altitude of 2,500 m for 3 h. Oxygen saturation, heart rate, and regional tissue saturation in the forehead (NIRS) were measured continuously. Before entering the chamber, after 90 and 180 min in the hypoxic environment, blood gas analysis and echocardiography were performed. Results Heart rate and blood pressure did not show significant intraindividual changes. Capillary oxygen saturation (SaO2) decreased significantly after 90 min by a mean of 5.6 ± 2.87% without further decline. Lactate, pH, base excess, and tissue saturation in the frontal brain did not reach any critical values. In the case of open fenestration between the tunnel and the atrium delta, P did not increase, indicating stable pulmonary artery pressure. Conclusion All 21 children finished the investigation successfully without any adverse events, so flying short distance seems to be safe for most Fontan patients with good current health status. As the baseline oxygen saturation does not allow prediction of the maximum extent of desaturation and adaption to a hypoxic environment takes up to 180 min, the so-called hypoxic challenge test is not sufficient for these patients. Performing an FTF examination over a period of 180 min allows for risk assessment and provides safety to the patients and their families, as well as the airline companies.